URGENSI SUPERVISI MANAJERIAL UNTUK PENINGKATAN KINERJA SEKOLAH - Rohmatika, Ratu Vina (Universitas Islam Negeri Raden Intan Lampung, 2016)
The focus of this paper is to analyze importanceof managerial supervision in improving schoolperformance. Based on the results, it can beconcluded that the supervisor plays a verystrategic in performing managerial supervisionfunctions in the school or madrasah. Asmanagerial supervisor, he is required to have theknowledge, attitudes, and skills in managementand leadership, so that it can play a role and itsfunction in assisting the headmasters in managing theresources of the school or madrasah efficientlyand effectively. Therefore, the regulation ofsupervisor criteria should be applied immediatelyto improve the the order of education in generaland school development in particular.